IMPLEMENTASI DATA MINING DALAM PENERBITAN SURAT PENETAPAN TARIF DAN NILAI PABEAN MENGGUNAKAN METODE CLASSIFICATION PADA DIREKTORAT JENDERAL BEA DAN CUKAI - Sri Lestari; Herta Apriani Silaban (CKI ON SPOT, 2018)
ABSTRACT Directorate General of Customs and Excise, which is an agency under the Ministry of Finance which has the duties and strategic functions in carrying out supervision in the field of export imports. Submission of customs documents is self assessment because only company know about the goods imported so needs to be inspected by Customs and Excise Officials. In the event that the customs inspection result is found a wrong notification, the Customs and Excise Officer will make a correction and be stated in a letter called Surat Penetapan Tarif dan Nilai Pabean (SPTNP). Data mining is a term used to describe the discovery of knowledge in a database. Data mining classification method using CRISP-DM research model can be used to provide predictions in the determination of SPTNP. Classification process is done by comparing three classification algorithms, namely Decision Tree, Naive Bayes, and Logistic Regression. The results of the classification process are evaluated using Confusion Matrix and T-Test to get the best accuracy logarithms. This research also uses Correlation Matrix to determine the relationship between factors.Keyword: Data Mining, Classification, CRISP-DM